Optimization of Conditions for Production of Lovastatin, A Cholesterol Lowering Agent, from a Novel Endophytic Producer Meyerozyma guilliermondii. Issue 3 (3rd May 2020) - Ravuri, Meena; Shivakumar, Srividya
Abstract: Lovastatin production through submerged fermentation has been widely studied while there are very few reports on the same through Solid State Fermentation (SSF). This study attempts to investigate the effect of various fermentation process parameters on lovastatin production from endophytic Meyerozyma guilliermondii through SSF. The parameters were optimized one at a time using wheat bran as substrate. It was found that 1g of wheat bran of mixed particle sizes moistened with 0.5 mL of distilled water with an initial pH 8.0, when inoculated with 0.5 mL of spore suspension containing approximately 10 6 spores/mL and incubated at 30°C gave an optimum yield of 3.5 mg/gds on day 8. Supplementation of wheat bran with various carbon sources (1 % w/w ) did not show any significant increase in the production while that with nitrogen sources (1 % w/w ) and sodium acetate (10-40 % w/w ) showed a repressive effect. However, addition of zinc sulphate (10 % w/w ), histidine (20 % w/w ), tween-80 (40 % v/w ) and B-group vitamins (40 % v/w ) yielded 18.25 mg/gds of lovastatin. Optimization of production parameters resulted in an overall 11.4 fold increase in lovastatin yield as compared to unoptimized conditions which favored 1.6 mg/gds.